2021
DOI: 10.1029/2020jd034474
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Closure of Surface Energy Balance Linked to Asymmetric Turbulent Transport of Scalars by Large Eddies

Abstract: How large turbulent eddies influence non‐closure of the surface energy balance is an active research topic that cannot be uncovered by the mean continuity equation in isolation. It is demonstrated here that asymmetric turbulent flux transport of heat and water vapor by sweeps and ejections of large eddies under unstable atmospheric stability conditions reduce fluxes. Such asymmetry causes positive gradients in the third‐order moments in the turbulent flux budget equations, primarily attributed to substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…This further reminds us to be cautious when applying MOST-based methods to determine scalar fluxes even under idealized conditions. The results highlight the importance of interactions between the CBL processes and the ASL turbulent exchanges, which in turn lead to changes in the ASL turbulence structures and fluxes (Cheng et al, 2021;Li et al, 2018Li et al, , 2021Liu et al, 2021). It should be noted that although other factors (e.g., surface heterogeneity) can also contribute to dissimilarities, the findings in this study can facilitate the understanding of the impact of surface heterogeneity on   E q dissimilarity, given that heterogeneous surface consists of patches with different  E , which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…This further reminds us to be cautious when applying MOST-based methods to determine scalar fluxes even under idealized conditions. The results highlight the importance of interactions between the CBL processes and the ASL turbulent exchanges, which in turn lead to changes in the ASL turbulence structures and fluxes (Cheng et al, 2021;Li et al, 2018Li et al, , 2021Liu et al, 2021). It should be noted that although other factors (e.g., surface heterogeneity) can also contribute to dissimilarities, the findings in this study can facilitate the understanding of the impact of surface heterogeneity on   E q dissimilarity, given that heterogeneous surface consists of patches with different  E , which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…Based on Equation (), the influence of vertical flux transport on local turbulent flux has been investigated using multi‐level EC measurements (Li et al ., 2018; Lan et al ., 2019; Liu et al ., 2021). The results found that the disproportionate changes in turbulent transport asymmetry with instability regulate the varying flux contributions and coincide with the widely observed increase in the non‐closure with increasing instability.…”
Section: Resultsmentioning
confidence: 99%
“…As a fundamental concept in the theoretical description of the global climate system, the surface energy balance (SEB), which depicts the energy exchange processes at the Earth's surface, has been extensively investigated for decades. The eddy covariance (EC) methodology is widely employed to directly measure turbulent heat fluxes, soil heat flux, and net radiation, supporting the assessment of the SEB on the local ecosystem scale (Baldocchi et al ., 2001; Mauder et al ., 2007; Oncley et al ., 2007; Liu et al ., 2021; Metzger et al ., 2021). The closure of the SEB is expected under the idealized circumstance that fluxes are perpendicular to the horizontally uniform two‐dimensional exchange surface without a canopy (Mauder et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the eddy covariance observations notoriously suffer from substantial biases and non-closure of the energy balance (Foken, 2008;Mauder et al, 2020). The non-closure of the energy balance is attributed to 1) large advective fluxes caused by surface, 2) systematic measurement errors due to mismatch in observation footprint or inadequate sample rate, 3) thermal processes, such as heat storage or vegetation metabolism (Mauder et al, 2020;Chu et al, 2021;Liu et al, 2021). The test sites in this study were selected to have a relatively homogeneous landcover.…”
Section: Observation Uncertaintiesmentioning
confidence: 99%